The Springs Restaurant, Cameron Shopping Center - Erwin Lang::::::photographer::: (1957)
Contact print containing four photographs of The Springs Restaurant in Palm Springs, CA. Views include an exterior shot, a shot inside the dining room, and two shots of the outdoor dining patio. Stamped "Erwin Lang" on back. Mosaic by Millard Sheets.